Nonatherosclerotic Obstructive Vascular Diseases of the Mesenteric and Renal Arteries. Issue 11 (6th August 2014) - Escárcega, Ricardo O.; Mathur, Moses; Franco, Joseph J.; Alkhouli, Mohamad; Patel, Chirdeep; Singh, Kanwar; Bashir, Riyaz; Patil, Pravin
Abstract Nonatherosclerotic vascular diseases of the mesenteric and renal arteries are considered to occur less frequently than those caused by occlusive atherosclerotic disease. However, when present, they pose a significant diagnostic and therapeutic challenge. Such disorders include fibromuscular dysplasia, median arcuate ligament syndrome, the renal nutcracker syndrome, and some forms of acute and chronic mesenteric ischemia (embolic and thrombotic). This is a heterogeneous group of disorders with substantial differences in the pathogenesis and diagnostic approaches to these diseases. We provide an overview of the pathogenesis, clinical presentation, diagnosis, and current management of fibromuscular dysplasia, median arcuate ligament syndrome, and the renal nutcracker syndrome.